Let the wave velocity is dependent on the tension and mass per unit length. Then
Since dimensions of velocity, force and mass per unit length are as follows,
"[F]=MLT^{-2}"
"[\\mu]=ML^{-1}"
we obtain
"LT^{-1}=\\left(MLT^{-2}\\right)^{\\alpha}(ML^{-1})^{\\beta}""LT^{-1}=M^{\\alpha+\\beta}L^{\\alpha-\\beta}T^{-2\\alpha}"
So
Solution
"\\left\\{\\begin{matrix}\n \\alpha &=& 1\/2\\\\\n \\beta &=& -1\/2\n\\end{matrix}\\right."
Finally
"v=F^{1\/2}\\mu^{-1\/2}=\\sqrt{\\frac{F}{\\mu}}"
Comments
Leave a comment